Systematiska felkällor i deklinationsdata från sedimentära borrkärnor - Belcher,Carl Nils (Examensarbeten i geologi vid Lunds universitet, 2025)
Declination data from cores from swedish lake sediments show a westward declination in the upper part of most cores. This does not align with paleomagnetic models and is therefore considered false. Using Microsoft Excel these false values have been corrected and used in a swedish version of FENNOSTACK called SWESTACK. SWESTACK gives a mean value with 95% confidence of the declination over the period from 9450 to -50 cal BP. The confidence interval of SWESTACKs declination has shown to be smaller than that of FENNOSTACK up until 350 cal BP. This increased precision of declination could result in future paleomagnetic models with higher resolution. Higher resolution models could advance scientists understanding of the processes behind the Earth's magnetic field. In doing so scientists could possibly be able to predict the future development of the South Atlantic Anomaly.
Keywords: paleomagnetism; declination; calibrating paleomagnetic data; SWESTACK; FENNOSTACK; the South Atlantic Anomaly (SAA)